Ocorrência de aves diurnas em matas primárias e secundárias na Amazônia Central - Freitas, Sandra Martins de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Secondary forests (SF) are expanding worldwide and replacing large areas of old growth forest (OG) in the tropics. Wildlife management thus requires knowledge of SF usage by OG fauna. Five recent reviews suggest that SF older than 20 years has similar richness to OG; nonetheless, the optimism of this message is still subject to confirmation because many studies are based on small sample sizes and/or lack the necessary analytical robustness. Aiming for a detailed understanding of SF use by birds in a highly diverse Amazon forest location, we test predictions about relative differences in site occupancy by 72 bird species in 107 OG and 44 mature (18-30 years) SF sites. We grouped species a priori into SF-prone, SFaverse, and Neutral, i.e. without any predicted occupancy difference between environments. Species detection data for the whole bird community were collected with autonomous recording devices between June and October 2010, with temporally replicated visits to each site. Using a hierarchical community model implemented in a Bayesian framework we explicitly accounted for the possibility of environmentrelated detection errors and estimated probabilities of site occupancy and detection for each species as well as for each group. Surprisingly, hypothetical SF-averse species occupied both environments with the same probability, even though their mean detection probability was lower in SF than in OG. Neutral group species had the lowest mean SF occupancy of all groups suggesting that our predictions might be based on limited natural history information. Our results also suggest that even though SF-averse species occupy SF they may be there in lower numbers than in OG. We conclude that mature SF in the proximity of old growth does provide habitat for OG species and should be protected.
Keywords: Aves; Habitat de aves; Distribuição espacial de aves